Efficacy and safety of endoscopic submucosal dissection for elderly patients with superficial squamous esophageal neoplasms. Issue 2 (1st April 2016) - Peng, Chunyan; Shen, Shanshan; Xu, Guifang; Lv, Ying; Zhang, Xiaoqi; Ling, Tingsheng; Wang, Lei; Ding, Xiwei; Zou, Xiaoping
Abstract : Background: Little is known about the outcomes of endoscopic submucosal dissection in elderly patients with superficial squamous esophageal neoplasms. Objective: To assess the efficacy and safety of endoscopic submucosal dissection for superficial squamous esophageal neoplasms in elderly patients (≥65 years) compared with non‐elderly patients. Methods: All patients with superficial squamous esophageal neoplasms receiving endoscopic submucosal dissection were retrospectively analyzed. Among them, 130 were aged 65 or older (group A), and 201 were aged younger than 65 years (group B). Therapeutic efficacy, adverse events, and follow‐up data were evaluated. Results: Group A had a higher prevalence of concomitant diseases than group B (52.3% vs. 14.9%, respectively). R0 resection rate was 82.3% in group A and 84.6 % in group B (P = 0.717). The curative resection rate was 80.8% in group A and 83.6% in group B (P = 0.653). The rate of procedure‐related non‐cardiopulmonary adverse events was 20.8% in group A and 16.9% in group B (P = 0.377). The incidence of cardiopulmonary adverse events during or after the procedure was 6.2% in group A and 2.5% in group B (P = 0.094). No procedure‐related mortality was reported in either group. Conclusion: Endoscopic submucosal dissection is effective and safe for treating superficial squamous esophageal neoplasms in elderly patients.